2019
DOI: 10.1177/0888406419883665
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Theory: The Missing Perspective in Teacher Education for Inclusion

Abstract: Our intergenerational authorial team takes up a central—and unresolved—issue within teacher education for inclusion, namely, the role of curriculum in reconceptualizing pre-service programs. We specifically review literature and policy on how special education teacher educators have approached conceptions of curriculum, using this past as prologue to argue that the teacher education curriculum requires a community of educators constructing a balance between a shared equity agenda to support the preparation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
0
29
0
2
Order By: Relevance
“…Thus, teachers’ attitudes, composed of three dimensions—cognitive (beliefs), affective (feelings) and behavioral (actions) [ 60 ]—are essential to achieve educational quality [ 2 ], although it should be noted that sometimes teachers are not sufficiently aware of the diversity of the needs of their students with disabilities [ 24 ]. Concerning self-efficacy, it has been reported that teachers with higher levels show greater job satisfaction, while those with lower levels of confidence in their abilities are associated with increased work-related stress and difficulties in coping with their tasks, including dealing with disruptive behaviors [ 65 ]. Thus, educational professionals’ preparation influences their attitudes, self-efficacy and their educational practices, so it is necessary to study current and future teachers’ perceptions about their own preparation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, teachers’ attitudes, composed of three dimensions—cognitive (beliefs), affective (feelings) and behavioral (actions) [ 60 ]—are essential to achieve educational quality [ 2 ], although it should be noted that sometimes teachers are not sufficiently aware of the diversity of the needs of their students with disabilities [ 24 ]. Concerning self-efficacy, it has been reported that teachers with higher levels show greater job satisfaction, while those with lower levels of confidence in their abilities are associated with increased work-related stress and difficulties in coping with their tasks, including dealing with disruptive behaviors [ 65 ]. Thus, educational professionals’ preparation influences their attitudes, self-efficacy and their educational practices, so it is necessary to study current and future teachers’ perceptions about their own preparation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…At best, individual critical teacher educators have attempted to infuse the existing curriculum with social justice and equityfocused content. However, these efforts do little overall to transform the minds and practices of teacher candidates towards advocacy for their future CLD students with various abilities (Pugach et al, 2020). This issue hinders the transformative struggle to engage in the work within teacher education programs.…”
Section: Discussionmentioning
confidence: 99%
“…Colorblind beliefs in special education can maintain white supremacy by creating confusion in both research and practice about the issue of disproportionality in special education (Artiles et al, 2010;Blanchett, 2006). These deficit views and colorblind ideologies are maintained in part because teacher education program lacks clear social justice and anti-racist focused curriculum (Pugach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por tal razón, una gran parte de la investigación actual pone énfasis en el impacto de la formación inicial y permanente como factor determinante para la práctica en el aula (Olson & Roberts 2018;Peebles & Mendaglio, 2014;Pegalajar & Colmenero, 2017;Sharma, 2018;Simón et al, 2018) en el ámbito de la inclusión y la diversidad humana (Paz, 2017). Se resalta la necesidad de impulsar programas de formación que preparen al docente para atender a la diversidad de forma más efectiva (Chiner et al, 2015) por medio de la reflexión sobre las barreras de aprendizaje, y generar un clima positivo de aula (Florian & Linklater 2010;Hamre & Oyler, 2004;Pugach et al, 2020).…”
Section: Las Creencias De Los Docentes Sobre La Inclusión Educativaunclassified